Severe atopic dermatitis and concurrent severe hidradenitis suppurativa successfully treated with dupilumab. (23rd September 2022) - Cho, Min Kyung; Shin, Jung U; Kim, Dong Hyun; Lee, Hee Jung
Abstract : We report a clinical experience of treating concomitant atopic dermatitis and hidradenitis suppurativa (HS) with dupilumab. This report is particularly noticeable in terms of disease severity and treatment duration compared to previous reported cases, suggesting long‐term dupilumab therapy can contribute to disease control even in patients with severe HS.